Moderating Role of Board Size between the Board Characteristics and the Bank’s Performance: Application of GMM - Eklemet, Ivy; Mohammed, Ibrahim; Gyamera, Emmanuel; Twumwaah, Deborah Adu (International Journal of Economics and Financial Issues, 2023)
The paper examines the moderating role of board size between board characteristics and the bank’s performance. The study collected data from 18 licensed banks in Ghana from 2012 to 2020, giving 180 observations for this study. The study adopted the System Generalized Method of Moments to assess the causal relationship between board characteristics and the bank’s performance in Ghana. The Generalized Method of Moments was adopted in this study to control the problems of endogeneity and unobserved heterogeneity issues. The findings show a significant relationship between board characteristics (non-executive directors, directors share ownership, and board gender diversity) and bank performance. The results also indicate that the board size moderates the positive relationship between board characteristics and the bank’s performance. Nonetheless, the interaction effect was stronger for the director’s share ownership than other board characteristics. The findings highlight that the board size moderates or enhances the relationship between board characteristics and the bank’s performance. Therefore, board size is an essential criterion for promoting gender diversity and non-executive directors on the board. Based on the results, the study recommends strengthening the board with competent non-executive directors and female directors to enhance the independence and effectiveness of the board to prevent opportunistic behaviors of managers espoused through agency theory.